Oversight Resulting in the Death of Others According to Article 359 of the Criminal Code - Keren Tendean; Jocefina A. Tendean; Arie M. Andes (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
As the times progress, more and more means of transportation are needed to meet the needs of humans. Mobility in traffic becomes an obstacle in dealing with vital error problems in traffic accidents. Indeed, such things cannot be denied in traffic, in intentional or even unintentional arrangements. Road traffic violations are actions or actions that are contrary to the provisions of traffic laws and regulations. In the Criminal Code (KUHP) criminal acts are divided into crimes (misdrijven) and violations (overtredingen). Cases of negligence that result in the death of other people are urgent matters to be discussed in a legal perspective, therefore the purpose of this paper is to find out the application of Article 359 of the Criminal Code so that people who commit criminal acts because their negligence causes people to die can be punished. In this study using normative legal research methods, which examines the law which is conceptualized as a norm or rule that applies in society and becomes a role model for everyone's behavior. The conclusion is that mistakes in criminal law are very important because a person cannot be convicted if he has no mistakes. And someone can be said to be guilty if he commits a crime, in a state of being able to take responsibility for what he has done intentionally or by negligence and there is no excuse for forgiveness.